Patatin‐like phospholipase 3 (rs738409) gene polymorphism is associated with increased liver enzymes in obese adolescents and metabolic syndrome in all ages. Issue 1 (5th May 2015) - Mangge, H.; Baumgartner, B. G.; Zelzer, S.; Prüller, F.; Schnedl, W. J.; Reininghaus, E. Z.; Haybaeck, J.; Lackner, C.; Stauber, R.; Aigner, E.; Weghuber, D.
Summary Background Obesity is associated with non‐alcoholic fatty liver disease (NAFLD), and the patatin‐like phospholipase 3 (PNPLA3) rs738409 (Ile148Met, C>G) gene polymorphism is one of the most important genetic determinants of NAFLD. Carriers have been reported to better respond to lifestyle modification. Aim To investigate the effect of rs738409 on overweight/obese adolescents and adults with and without metabolic syndrome (MetS). Methods Two hundred and eighty‐eight overweight/obese and 209 normal weight participants of the STYJOBS/EDECTA cohort (NCT00482924) were analysed for PNPLA3 genotypes. Results Compared to overweight/obese without MetS, in overweight/obese study participants with MetS, the presence of the G allele (148Met) was significantly higher (CC: 5.0% vs. 9.2%, Spearman's correlation, 0.12; P = 0.038). Persons with CG (heterozygote for the risk allele) and with GG (homozygote for the risk allele) genotypes showed significantly higher ALT levels than those with CC genotypes. Even young individuals aged below 20 years had significantly increased ALT levels if they were homozygote with the G allele. Conclusions The PNPLA3 rs738409 polymorphism is associated already in youths with increased ALT, and is more frequent in obese with MetS of all ages. Hence, overweight/obese rs738409 carriers should be identified early in life and treated with a rigorous life style intervention.